Discourse and decolonization: analyzing the impact of colonial history and culture on African leadership narratives - Maqashalala, Xatyiswa (My University, 2025)
This qualitative research study explored how colonial history and culture have shaped African leadership, while also examining how African traditions, philosophies, and values can inform the development of inclusive leadership models relevant to the African context. Focusing on South Africa, a nation with a history of colonialism and apartheid, the study analyzed the discourse of community leaders during the transition from apartheid to democracy. Participants in various leadership roles engaged with the research to address overarching questions about the enduring influence of colonial legacies on leadership practices and the potential of African traditions to foster more inclusive and culturally relevant governance. Sub-questions investigated key elements of traditional African leadership, the ongoing impact of colonialism on current structures, and the benefits of integrating indigenous values into leadership frameworks for improved community engagement and governance outcomes. The study was grounded in the theoretical frameworks of social constructionism, critical social theory, and decolonization, which provided a vigorous foundation for critically examining the interplay between colonial history, cultural identity, and leadership practices. Discourse analysis was employed as the primary methodology, enabling the study to uncover hidden power dynamics, cultural disconnects, and transformative pathways for decolonizing leadership. This approach aligned with the study’s emphasis on context, meaning-making, and the reclamation of indigenous knowledge systems. The findings, derived from discourse analysis, revealed four major themes: (1) colonialism as a persistent force in African leadership, (2) traditional African leadership as a foundation for inclusive governance, (3) the disconnect between contemporary leadership and African cultural values, and (4) decolonization as a pathway to inclusive and responsive leadership. These themes highlight the enduring impact of colonial legacies while also pointing to the transformative potential of integrating African traditions and philosophies into modern governance. The study contributes constructive insights for reimagining African leadership in ways that are inclusive, culturally relevant, and responsive to the needs of local communities, offering a roadmap for decolonizing leadership practices across the continent.
Keywords: Decolonization; African leadership; Colonial legacies; Discourse analysis; Apartheid